PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK PADA MATERI PENCEMARAN LINGKUNGAN (Studi Eksperimen di Kelas X SMA Negeri 1 Cihaurbeuti Tahun Ajaran 2015/2016) - Surahman, Endang; Fitri, Anne Novia (LP3MPM Universitas Siliwangi, 2016)
Abstract: The aimed of this research was to know the influence of problem based learning model to creative thinking skills on environmental pollution material in X grade of SMA Negeri 1 Cihaurbeuti at 2015/2016 academic year. This research was conducted from November 2015 until March 2016 in X grade of SMA Negeri 1 Cihaurbeuti. The method used in this research was true experiment. The population of this research was all class of X grade at SMA Negeri 1 Cihaurbeuti as much as 4 classes which consist of 144 student. The sample used in the research which taken by cluster random sampling technique as much as two class, X MIPA 1 as the experimental class and X MIPA 2 as the control class. To measure the creative thingking skills, used an instrument that is a test of the creativethingking skills which consists of 11 questions in the form of essay. Analysis using t test with significance level α = 0,05. The result of the research shows there was influence of problem based learning model to creative thinking skills on environmental pollution material (an experimental study in X grade of SMA Negeri 1 Cihaurbeuti academic year 2015/2016.